2020
DOI: 10.1186/s13023-020-1347-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding acute metabolic decompensation in propionic and methylmalonic acidemias: a deep metabolic phenotyping approach

Abstract: Background: Pathophysiology of life-threatening acute metabolic decompensations (AMD) in propionic acidemia (PA) and isolated methylmalonic acidemia (MMA) is insufficiently understood. Here, we study the metabolomes of PA and MMA patients over time, to improve insight in which biochemical processes are at play during AMD. Methods: Longitudinal data from clinical chemistry analyses and metabolic assays over the life-course of 11 PA and 13 MMA patients were studied retrospectively. Direct-infusion high-resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…10 In particular, the relative depletion of glutamine in organic acidurias may result from the attempt of replenish alphaketoglutarate in the Krebs cycle. 10,14 In our study, we observed that MCA was directly related also to plasma lysine and glycine levels. Lysine is an essential amino acid and its increase likely reflects a decreased degradation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…10 In particular, the relative depletion of glutamine in organic acidurias may result from the attempt of replenish alphaketoglutarate in the Krebs cycle. 10,14 In our study, we observed that MCA was directly related also to plasma lysine and glycine levels. Lysine is an essential amino acid and its increase likely reflects a decreased degradation.…”
Section: Discussionsupporting
confidence: 54%
“…Correlation analysis between MCA with other metabolic parameters displayed the significant correlation with plasma ammonia levels, a result in line with previous studies, that confirms the perturbation of ammonia metabolism in inherited disorders of propionate. 10,11,14 Furthermore, plasma MCA was also positively correlated with lysine and glycine levels as well as with the changes in acyl-carnitine profile (C3 and C3/C2 and C3/C16 ratios), reflecting the mitochondrial accumulation of propionyl-CoA and the relative depletion of acetyl-CoA.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Appropriate management of acute metabolic crises is crucial for normal intellectual development in PA patients [ 4 ]. Recent literature confirms that hyperammonemia and metabolic decompensation have a great impact on patients’ outcome, and that even when diagnosis is a result of NBS, outcomes are not necessarily better [ 7 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute decompensations, whose initial management is critical, can be triggered by fever, vomiting, prolonged fasting, gastroenteritis and other infections [ 5 , 6 ]. The health gains of NBS for PA in overall outcome are modest, even if mortality in patients detected by NBS is lower than in the group detected by selected metabolic screening [ 3 , 5 7 ].…”
Section: Introductionmentioning
confidence: 99%